Casearia Essential Oil: An Updated Review on the Chemistry and Pharmacological Activities - Alexandre Carvalho, Flavio [UNESP]; Valadares de Moraes, Natália; Eduardo Miller Crotti, Antônio; José Crevelin, Eduardo; Gonzaga dos Santos, André [UNESP] (Wiley, 2023)
Casearia species are found in the America, Africa, Asia, and Australia and present pharmacological activities, besides their traditional uses. Here, we reviewed the chemical composition, content, pharmacological activities, and toxicity of the essential oils (EOs) from Casearia species. The EO physical parameters and leaf botanical characteristics were also described. The bioactivities of the EOs from the leaves and their components include cytotoxicity, anti-inflammatory, antiulcer, antimicrobial, antidiabetic, antioxidant, antifungal, and antiviral activities. The main components associated with these activities are the α-zingiberene, (E)-caryophyllene, germacrene D, bicyclogermacrene, spathulenol, α-humulene, β-acoradiene, and δ-cadinene. Data on the toxicity of these EOs are scarce in the literature. Casearia sylvestris Sw. is the most studied species, presenting more significant pharmacological potential. The chemical variability of EOs components was also investigated for this species. Caseria EOs have relevant pharmacological potential and must be further investigated and exploited.
Keywords: natural products; phytochemistry; Salicaceae; var. lingua; var. sylvestris